Apresentação - Machado Ferrari, Ana Carolina; Pereira, Denilson Diniz; Sá, Michele Aparecida de; Rahme, Mônica Maria Farid (Revista Educação, Pesquisa e Inclusão, 2020)
Textos de apresentação dos artigos que compõe a edição temática.